From Text to Context: Fazlur Rahman's Double Movement Theory in Contemporary Qibla Direction Issues - Hendri Hendri; Saiful Amin (Islamic Astronomy Department, Sharia and Law Faculty, 2025)
Qibla direction determination is an important part of Muslim worship that signifies unity of direction and obedience to Allah SWT. However, in the development of modern science and technology, there are differences in the methods and results of determining the Qibla direction in various regions of the Islamic world. This problem requires a dynamic interpretation approach, so that the values of the Qur'an can be understood and applied according to the context of the times. This research uses Fazlur Rahman's hermeneutic approach with Double Movement theory to interpret the verses about Qibla direction. The results show that the Qibla direction is not just a matter of geographical precision, but a symbol of unity, independence, and spiritual orientation of Muslims. With the application of Double Movement, the moral values of the Qur'an can be actualized through the use of modern technology in a maslahat manner and in accordance with the objectives of sharia. in the application of the discovery method.